DIPLOMASI PUBLIK MALAYSIA TERHADAP PREFERENSI TUJUAN KERJA MASYARAKAT PERBATASAN INDONESIA-MALAYSIA DI KECAMATAN RUPAT UTARA - Yudha Pratama; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The purpose of this study is to find out about the form of diplomacy carried out by Malaysia against The purpose of this study is to find out about the form of diplomacy carried out by Malaysia against border communities, especially the North Rupat community. As a border community in the outermost region of Indonesia, relying solely on their own area as a place of economic activity is not a good choice, apart from not having many job choices, their income tends to be lower. Therefore, many people choose to work outside the region and even abroad, one of which is Malaysia.This study starts from the role of Malaysia as a recipient and contributor of foreign workers, but from these two roles Malaysia is seen as more popular as a recipient country for foreign workers. In the case of Indonesia, especially North Rupat, this is the main active contributor to Malaysia's foreign workforce.This research uses constructivism perspective, public diplomacy theory and uses three concepts of Soft Power Currencies by Alexander Vuving. brilliance, beauty, and benignity. Beauty is the resonance of shared norms and goals, brilliance is the attraction that results from ability and success, and benignity is the visible goodness of behavior and attitude. The method used is a qualitative method. Data collection techniques include literature studies from several journals, books, documents, websites and interviews.The results of this study conclude that Malaysian Diplomacy through the three concepts of soft power currency can be a factor that attracts foreign workers, especially workers from North Rupat to seek economic opportunities in Malaysia. Keywords: Malaysia, Foreign Workers, North Rupat, Soft Power Currency, Public